How robust is the uniform emissions pricing rule to social equity concerns? - Abrell, Jan; Rausch, Sebastian; Schwarz, Giacomo (Journal of environmental economics and management, 2018)
This paper examines pollution tax differentiation across industries in light of social equity concerns using theoretical and numerical general equilibrium analyses in an optimal tax framework. We characterize the drivers for non-uniform optimal taxes stemming from the interaction of household heterogeneity with social preferences. Quantitatively assessing the case of price-based CO2 emissions control in the U.S. economy, we find that uniform emissions pricing is approximately optimal when social concerns are defined over inequity induced by the environmental tax. The deviation from uniform emissions pricing, however, becomes non-negligible when pollution tax rebates deviate much from optimal transfer schemes or when social concerns are defined over both policy-induced impacts and inequity unrelated to environmental policy. Our results are robust to a number of model extensions including the stringency of the environmental target, downstream vs. upstream taxation, pre-existing distortionary taxes, and parametric uncertainty in firms’ and households’ equilibrium tax responses.